Tropical Poultry Genetic Solutions: Where science meets smallholder needs - International Livestock Research Institute (International Livestock Research Institute, 2025)
In this short video, we take you inside ILRI’s poultry research facility in Addis Ababa, Ethiopia – an advanced poultry research and training centre.